Convex and non-convex approaches for cost efficiency models with fuzzy data. (2015) - Paryab, Khalil; Tavana, Madjid; Shiraz, Rashed Khanjani
Classical cost efficiency (CE) measurement models require exact and accurate knowledge of the input and output values for each decision making unit (DMU). However, the observed values of the input and output data in real-world problems are often imprecise or vague. In recent years, fuzzy data envelopment analysis (DEA) has been successfully used to deal with imprecise or vague data in efficiency measurement. In this paper, we incorporate fuzzy set theory into the traditional CE measurement. We propose two approaches based on the convex DEA and non-convex free disposable hull (FDH) approach with fuzzy variables. The purpose of this paper is two-fold: 1) we develop a CE analysis for non-parametric convex methods based on fuzzy set theory; 2) we further develop a non-convex CE analysis model where the non-convexity is formulated based on the FDH approach. We also present a numerical example to demonstrate the applicability of the proposed models and exhibit the efficacy of the procedures and algorithms.